Composition Analysis in Unknown Contexts - Wehrheim, Heike; Hüllermeier, Eyke; Becker, Steffen; Becker, Matthias; Richter, Cedric; Sharma, Arnab (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Mitigating Label Noise through Data Ambiguation - Lienen, Julian; Hüllermeier, Eyke (arXiv:2305.13764)
Label noise poses an important challenge in machine learning, especially in deep learning, in which large models with high expressive power dominate the field. Models of that kind are prone to memorizing incorrect labels, thereby harming generalization performance. Many methods have been proposed to address this problem, including robust loss functions and more complex label correction approaches. Robust loss functions are appealing due to their simplicity, but typically lack flexibility, while label correction usually adds substantial complexity to the training setup. In this paper, we suggest to address the shortcomings of both methodologies by "ambiguating" the target information, adding additional, complementary candidate labels in case the learner is not sufficiently convinced of the observed training label. More precisely, we leverage the framework of so-called superset learning to construct set-valued targets based on a confidence threshold, which deliver imprecise yet more reliable beliefs about the ground-truth, effectively helping the learner to suppress the memorization effect. In an extensive empirical evaluation, our method demonstrates favorable learning behavior on synthetic and real-world noise, confirming the effectiveness in detecting and correcting erroneous training labels.

Reconfigurable Random Forest Implementation on FPGA - Raeisi Nafchi, Masood

Data Analytics for Predictive Maintenance of Time Series Data - Yadalam Murali Kumar, Nihal

Design approach to extend and decarbonise existing district heating systems - case study for German cities - Divkovic, Denis; Knorr, Lukas; Meschede, Henning (International Journal of Sustainable Energy Planning and Management)
This paper aims to present an approach for the planning of carbon low heat supply in a future district heating system based on open data for German cities with existing district heating networks. One focus is on the integration of industrial waste heat and the uncertainty of future waste heat sources as well as restrictions on the use of biomass. For that purpose, knowledge about the energy demand is necessary. In a first step it is shown how the demand around a heating network is estimated with spatial data and a load profile is generated. Local available heat sources are examined according to their suitability and their kind of integration in the heating network. As heat production from different units are optimised, the development of a simulation model will be presented. The simulation is based on the optimisation of the operational costs of the used technologies for heating supply. Different scenarios covering various technologies and economic assumptions are applied. The results show the levelized costs of heating as well as the ecological performance. A sensitivity analysis shows the importance of uncertainties for the economic assumptions. The results showing levelized costs of heating as well as the ecological performance underlining the advantage of excess heat integration.
Keywords: Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

„Löwenstark in der Schwangerschaft!“ Ressourcenaktivierung und Stressreduktion mit dem Zürcher Ressourcen Modell (ZRM®) – eine unkontrollierte Interventionsstudie - Schneider, Tamara; Weber, Julia; Bauer, Nicola H. (Prävention und Gesundheitsförderung)
Jede Schwangerschaft bringt physische, psychische und soziale Veränderungen mit sich. Diese können zu Stress und ambivalenten Gefühlen bei Schwangeren führen, die einen starken Einfluss auf das Wohlbefinden und die Gesundheit von Mutter und Kind haben. Zur Förderung eines komplikationslosen Verlaufs der Schwangerschaft wird in der Forschungsliteratur die Stärkung der gesundheitlichen Ressourcen gefordert. Das Zürcher Ressourcen Modell (ZRM) ist ein ressourcenaktivierendes Selbstmanagementtraining, welches nach aktuellen Studienergebnissen die Gefühlsregulierung unterstützen und Stress reduzieren kann. Ziel dieser Studie war die erstmalige Wirksamkeitsprüfung des ZRM in der Schwangerschaft. Angenommen wurde, dass durch die Aktivierung der persönlichen Ressourcen der Schwangeren das Stresserleben reduziert und das subjektive Wohlbefinden gesteigert werden kann. Die Konstrukte „Stress“ und „Wohlbefinden“ wurden anhand von fünf psychometrischen Parametern operationalisiert. Durchgeführt wurde eine quasiexperimentelle unkontrollierte 6‑stündige Online-Interventionsstudie mit dem ZRM im Januar 2021 an N = 32 Schwangeren, basierend auf einem Prä-Post-Follow-up-Design. Zur Überprüfung der gebildeten Hypothesen wurden einfaktorielle Varianzanalysen (rmANOVAs) durchgeführt. Die 1-faktoriellen rmANOVAs ergaben, dass die ZRM-Intervention das Stresserleben allgemein und schwangerschaftsspezifisch sowie das Angsterleben signifikant senken konnte. Handlungsorientierung nach Misserfolg und emotionales Wohlbefinden konnten signifikant gesteigert werden. Hinsichtlich der subjektiven Vitalität ließ sich lediglich deskriptiv eine Steigerung der Werte verzeichnen. Die ZRM-Intervention erwies sich als wirksame Methode zur Optimierung der Stressbewältigung und Steigerung des Wohlbefindens während der Schwangerschaft. Es kann zielführend sein, das ZRM-Training als Ergänzung zur üblichen Geburtsvorbereitung einzusetzen. Zukünftige Forschungsarbeiten sollten v. a. die Übertragbarkeit der Ergebnisse unter Einbindung einer Kontrollgruppe sicherstellen.
Keywords: Public Health; Environmental and Occupational Health

The Optimal Depth of Variational Quantum Algorithms Is QCMA-Hard to Approximate - Bittel, Lennart; Gharibian, Sevag; Kliesch, Martin (Proceedings of the 38th Computational Complexity Conference (CCC))
Variational Quantum Algorithms (VQAs), such as the Quantum Approximate Optimization Algorithm (QAOA) of [Farhi, Goldstone, Gutmann, 2014], have seen intense study towards near-term applications on quantum hardware. A crucial parameter for VQAs is the depth of the variational ansatz used - the smaller the depth, the more amenable the ansatz is to near-term quantum hardware in that it gives the circuit a chance to be fully executed before the system decoheres. This potential for depth reduction has made VQAs a staple of Noisy Intermediate-Scale Quantum (NISQ)-era research. In this work, we show that approximating the optimal depth for a given VQA ansatz is intractable. Formally, we show that for any constant $ε>0$, it is QCMA-hard to approximate the optimal depth of a VQA ansatz within multiplicative factor $N^{1-ε}$, for $N$ denoting the encoding size of the VQA instance. (Here, Quantum Classical Merlin-Arthur (QCMA) is a quantum generalization of NP.) We then show that this hardness persists even in the "simpler" setting of QAOAs. To our knowledge, this yields the first natural QCMA-hard-to-approximate problems. To achieve these results, we bypass the need for a PCP theorem for QCMA by appealing to the disperser-based NP-hardness of approximation construction of [Umans, FOCS 1999].

Zur Darstellung der Afrikanischen Europäerin in Geschichte und Gegenwart - Sharon Dodua Otoos Roman 'Adas Raum' - Müller, Inez (Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

Empirical Analysis in Markets for OTF Services - Elrich, Alina; Kaimann, Daniel; Fahr, René; Kundisch, Dennis; Mir Djawadi, Behnud; Müller, Michelle; Poniatowski, Martin; Schäfers, Sabrina; Frick, Bernd (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Engineering Sub‐Nanometer Hafnia‐Based Ferroelectric to Break The Scaling Relation for High‐Efficiency Piezocatalytic Water Splitting - Su, Ran; Zhang, Jiahui; Wong, Vienna; Zhang, Dawei; Yang, Yong; Luo, Zheng‐Dong; Wang, Xiaojing; Wen, Hui; Liu, Yang; Seidel, Jan; Yang, Xiaolong; Pan, Ying; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Die junge Käthe Kollwitz in ihrer künstlerischen Findungsphase - Schreckenberg, Carolin

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Anticipatory Assignment of Passengers to Meeting Points for Taxi-Ridesharing - Dieter, Peter; Stumpe, Miriam; Ulmer, Marlin Wolf; Schryen, Guido (Transportation Research Part D)

Cation-dependent assembly of hexagonal DNA origami lattices on SiO2 surfaces - Pothineni, Bhanu Kiran; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures have emerged as functional materials for applications in various areas of science and technology. In particular, the transfer of the DNA origami shape into inorganic materials using...
Keywords: General Materials Science

On Cloud Assisted, Restricted, and Reosurce Constrained Scheduling - Pukrop, Simon

Utilizing Redundancy in Distributed Heterogeneous Storage - Schneider, Fabian

Gelingensbedingungen gestaltungsorientierter Schulentwicklung - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (Organisation zwischen Theorie und Praxis)

Potenziale der Kulturerbe-Konvention von 2003. Beispiele aus der Beratungspraxis der Landesstelle Immaterielles Kulturerbe NRW - Harnack, Maria (Kulturerbe als kulturelle Praxis – Kulturerbe in der Beratungspraxis)

Peers: Powerful or Negligible? A Systematic Review on Peer Factors and Internal Whistleblowing - Mir Djawadi, Behnud; Plaß, Sabrina; Schäfers, Sabrina (Organizational Wrongdoing as the “Foundational” Grand Challenge: Consequences and Impact)

Graph Neural Network-based Anomaly Detection in Smart Grid Energy Consumption - Ranade, Amruta

Highly accurate deep compressed facial recognition - Ali, Osama

Super-Gaussian decay of exponentials: A sufficient condition - Hinrichs, Benjamin; Janssen, Daan W.; Ziebell, Jobst (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Tagungsbericht: 10/20 Jahre UNESCO-Konvention zum Erhalt des Immateriellen Kulturerbes – Auftaktveranstaltung zum Doppeljubiläum - Leineweber, Jonas

Politisches Graffiti (Kunst und Politik)

The Omnipotence (al-qudra) and the Will of God (al-irāda) in the Theology of Sayf ad-Dīn al-Āmidī - Husic, Ahmed (The Attributes of God in Islamic Thought: Contemplating Allah)

Virtual On-Demand Volunteer System Based on Delaunay Triangulation - Ashri, Nivedita

Temperedness of locally symmetric spaces: The product case - Weich, Tobias; Wolf, Lasse L. (arXiv:2304.09573)
Let $X=X_1× X_2$ be a product of two rank one symmetric spaces of non-compact type and $Γ$ a torsion-free discrete subgroup in $G_1× G_2$. We show that the spectrum of $Γ \backslash X$ is related to the asymptotic growth of $Γ$ in the two direction defined by the two factors. We obtain that $L^2(Γ \backslash G)$ is tempered for large class of $Γ$.

Arm und ausgegrenzt. Kinderarmut in der Literatur und im lesenden Klassenzimmer. - Kruse, Iris; Terhorst, Sarah („So viel Größenwahn muss sein!”)

Home-Based Measurements of Nocturnal Cardiac Parasympathetic Activity in Athletes during Return to Sport after Sport-Related Concussion - Delling, Anne Carina; Jakobsmeyer, Rasmus; Coenen, Jessica; Christiansen, Nele; Reinsberger, Claus (Sensors)
Sport-related concussions (SRC) are characterized by impaired autonomic control. Heart rate variability (HRV) offers easily obtainable diagnostic approaches to SRC-associated dysautonomia, but studies investigating HRV during sleep, a crucial time for post-traumatic cerebral regeneration, are relatively sparse. The aim of this study was to assess nocturnal HRV in athletes during their return to sports (RTS) after SRC in their home environment using wireless wrist sensors (E4, Empatica, Milan, Italy) and to explore possible relations with clinical concussion-associated sleep symptoms. Eighteen SRC athletes wore a wrist sensor obtaining photoplethysmographic data at night during RTS as well as one night after full clinical recovery post RTS (>3 weeks). Nocturnal heart rate and parasympathetic activity of HRV (RMSSD) were calculated and compared using the Mann–Whitney U Test to values of eighteen; matched by sex, age, sport, and expertise, control athletes underwent the identical protocol. During RTS, nocturnal RMSSD of SRC athletes (Mdn = 77.74 ms) showed a trend compared to controls (Mdn = 95.68 ms, p = 0.021, r = −0.382, p adjusted using false discovery rate = 0.126) and positively correlated to “drowsiness” (r = 0.523, p = 0.023, p adjusted = 0.046). Post RTS, no differences in RMSSD between groups were detected. The presented findings in nocturnal cardiac parasympathetic activity during nights of RTS in SRC athletes might be a result of concussion, although its relation to recovery still needs to be elucidated. Utilization of wireless sensors and wearable technologies in home-based settings offer a possibility to obtain helpful objective data in the management of SRC.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Coherent driving of direct and indirect excitons in a quantum dot molecule - Bopp, Frederik; Schall, Johannes; Bart, Nikolai; Vögl, Florian; Cullip, Charlotte; Sbresny, Friedrich; Boos, Katarina; Thalacker, Christopher; Lienhart, Michelle; Rodt, Sven; Reuter, Dirk; Ludwig, Arne; et al. (Physical Review B)

Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

"So viel Größenwahn muss sein!". Zur Einführung. - Kruse, Iris; Kanning, Julian (So viel Größenwahn muss sein! Kinderliteratur, Schule und Gesellschaft. Zum Bildungsauftrag des Literaturunterrichts in der Grundschule.)

Geschlechterspezifische Effekte in der bewegungstherapeutischen Behandlung von hämodynamischen Regulationsstörungen bei Morbus Parkinson - Siche-Pantel, Franziska; Jakobsmeyer, Rasmus; Buschfort, Rüdiger; Mühlenberg, Manfred; Michels, Heinke; Oesterschlink, Julian; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Motorische Symptome bei Morbus Parkinson lassen sich durch körperliche Aktivität modifizieren. Inwiefern dies auch für nicht-motorische, autonome Symptome gilt, ist weitaus weniger bekannt. Die Erkrankung weist zudem eine Vielzahl an geschlechterspezifischen Unterschieden auf. Epidemiologische Untersuchungen deuten zum Beispiel auf einen besseren primärpräventiven Effekt durch körperliche Aktivität bei Männern als bei Frauen hin. Daten zu geschlechterspezifischen Effekten auf das autonome Nervensystem sind jedoch limitiert. Im Rahmen der vorliegenden Pilotstudie sollen mögliche geschlechterspezifische Effekte einer Bewegungsintervention auf Störungen der hämodynamischen Regulation als Manifestation nicht-motorischer Symptome untersucht werden. Diese sind aufgrund ihrer oft gegensätzlichen hypo- und hypertonen Ausprägung schwierig medikamentös zu behandeln, lassen sich aber gegebenenfalls durch Bewegungsinterventionen modifizieren. Methodik Bei 42 Patienten und Patientinnen (Alter: 70,3 Jahre; 24 Männer; 18 Frauen) wurden vor und nach einer mehrwöchigen, stationären Parkinsonkomplexbehandlung hämodynamische Parameter in einem Schellongtest untersucht. Mittels anschließender Regressionsanalyse erfolgte eine Quantifizierung der Abhängigkeit von den Faktoren Alter, Body Mass Index, Krankheitsdauer, Vorerkrankungen, Sitzendblutdruck und hypotensiv wirkender Medikamente. Ergebnis Bei 44% der Männer und 46% der Frauen traten hämodynamische Regulationsstörungen im Stand und in Rückenlage mindestens einmal auf. Eine vor Therapiebeginn präsentierte Regulationsstörung im Stand zeigte sich in keiner Geschlechtergruppe durch die Parkinsonkomplexbehandlung verändert. Frauen zeigten zu Therapieende jedoch einen signifikant niedrigeren Blutdruck im Liegen (p=0,022*). Unabhängig von der Komplextherapie fiel der Blutdruck in Rückenlage bei Frauen nach Orthostasebelastung höher aus als davor (vor Therapie: p=0,015 *; nach Therapie: p=0,021*). Jedes Lebensjahr erhöhte das Risiko für eine hämodynamische Regulationsstörung in Rückenlage in der Gesamtgruppe um 12,4% (Regressionskoeffizient B=0,117; p=0,014 *; Exp(B)=1,124). Schlussfolgerung Systematische Effekte auf Blutdruckwerte im Rahmen von Orthostasereaktionen durch eine Parkinsonkomplexbehandlung konnten nicht nachgewiesen werden. Allerdings zeigte sich bei Frauen nach Parkinsonkomplexbehandlung eine Senkung der Blutdruckwerte in Rückenlage. Das scheinbar unsystematische, teils geschlechterspezifische Auftreten hämodynamischer Regulationsstörungen fordert ein individualmedizinisch angelegtes Vorgehen im therapeutischen Alltag.
Keywords: General Medicine

Fully guided and phase locked Ti:PPLN waveguide squeezing for applications in quantum sensing - Domeneguetti, Renato; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas S.; Gehring, Tobias (Optics Letters)
This work reports a fully guided setup for single-mode squeezing on integrated titanium-indiffused periodically poled nonlinear resonators. A continuous-wave laser beam is delivered and the squeezed field is collected by single-mode fibers; up to −3.17(9) dB of useful squeezing is available in fibers. To showcase the usefulness of such a fiber-coupled device, we applied the generated squeezed light in a fiber-based phase sensing experiment, showing a quantum enhancement in the signal-to-noise ratio of 0.35 dB. Moreover, our investigation of the effect of photorefraction on the cavity resonance condition suggests that it causes system instabilities at high powers.
Keywords: Atomic and Molecular Physics; and Optics

Finite Set Sensorless Control With Minimum a Priori Knowledge and Tuning Effort for Interior Permanent Magnet Synchronous Motors - Brosch, Anian; Tinazzi, Fabio; Wallscheid, Oliver; Zigliotto, Mauro; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Das DigitELE Tutorial: Eine digitale Lernumgebung in der Englischdidaktik - Janzen, Thomas; Gabel, Stephan; Gampert, Martha; Matz, Frauke; Reckermann, Julia (Digitalisierung in der Hochschullehre – Perspektiven und Gestaltungsoptionen)

SIMULATeQCD: A simple multi-GPU lattice code for QCD calculations - Mazur, Lukas; Bollweg, Dennis; Clarke, David A.; Altenkort, Luis; Kaczmarek, Olaf; Larsen, Rasmus; Shu, Hai-Tao; Goswami, Jishnu; Scior, Philipp; Sandmeyer, Hauke; Neumann, Marius; Dick, Henrik; et al. (Computer Physics Communications)
The rise of exascale supercomputers has fueled competition among GPU vendors, driving lattice QCD developers to write code that supports multiple APIs. Moreover, new developments in algorithms and physics research require frequent updates to existing software. These challenges have to be balanced against constantly changing personnel. At the same time, there is a wide range of applications for HISQ fermions in QCD studies. This situation encourages the development of software featuring a HISQ action that is flexible, high-performing, open source, easy to use, and easy to adapt. In this technical paper, we explain the design strategy, provide implementation details, list available algorithms and modules, and show key performance indicators for SIMULATeQCD, a simple multi-GPU lattice code for large-scale QCD calculations, mainly developed and used by the HotQCD collaboration. The code is publicly available on GitHub.

Viscosity of pure-glue QCD from the lattice - Altenkort, Luis; Eller, Alexander M.; Francis, Anthony; Kaczmarek, Olaf; Mazur, Lukas; Moore, Guy D.; Shu, Hai-Tao (Physical Review D)

Feministische Neomaterialismen: Die ontologische Immanenz und posthumanistische Performativität von Natur, Kultur und Technik - Kostan, Anastassija (Widerständige Glieder. Der Leib als politischer Standort)

Multi-FPGA Designs and Scaling of HPC Challenge Benchmarks via MPI and Circuit-Switched Inter-FPGA Networks - Meyer, Marius; Kenter, Tobias; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems)
While FPGA accelerator boards and their respective high-level design tools are maturing, there is still a lack of multi-FPGA applications, libraries, and not least, benchmarks and reference implementations towards sustained HPC usage of these devices. As in the early days of GPUs in HPC, for workloads that can reasonably be decoupled into loosely coupled working sets, multi-accelerator support can be achieved by using standard communication interfaces like MPI on the host side. However, for performance and productivity, some applications can profit from a tighter coupling of the accelerators. FPGAs offer unique opportunities here when extending the dataflow characteristics to their communication interfaces. In this work, we extend the HPCC FPGA benchmark suite by multi-FPGA support and three missing benchmarks that particularly characterize or stress inter-device communication: b_eff, PTRANS, and LINPACK. With all benchmarks implemented for current boards with Intel and Xilinx FPGAs, we established a baseline for multi-FPGA performance. Additionally, for the communication-centric benchmarks, we explored the potential of direct FPGA-to-FPGA communication with a circuit-switched inter-FPGA network that is currently only available for one of the boards. The evaluation with parallel execution on up to 26 FPGA boards makes use of one of the largest academic FPGA installations.
Keywords: General Computer Science

Lerngegenstand „Doppelkonsonanz“ in der Grundschule: Explizites und implizites Lernen im Längsschnitt - Topalović, Elvira; Drepper, Laura; Härtel, Kira (Schriftspracherwerb im Spannungsfeld zwischen Wissen und Können)

Towards Comparable Ratings: Quantifying Evaluative Phrases in Physician Reviews - Kersting, Joschka; Geierhos, Michaela (Data Management Technologies and Applications)
We present a concept for quantifying evaluative phrases to later compare rating texts numerically instead of just relying on stars or grades. We achievethis by combining deep learning models in an aspect-based sentiment analysis pipeline along with sentiment weighting, polarity, and correlation analyses that combine deep learning results with metadata. The results provide new insights for the medical field. Our application domain, physician reviews, shows that there are millions of review texts on the Internet that cannot yet be comprehensively analyzed because previous studies have focused on explicit aspects from other domains (e.g., products). We identify, extract, and classify implicit and explicit aspect phrases equally from German-language review texts. To do so, we annotated aspect phrases representing reviews on numerous aspects of a physician, medical practice, or practice staff. We apply the best performing transformer model, XLM-RoBERTa, to a large physician review dataset and correlate the results with existing metadata. As a result, we can show different correlations between the sentiment polarity of certain aspect classes (e.g., friendliness, practice equipment) and physicians’ professions (e.g., surgeon, ophthalmologist). As a result, we have individual numerical scores that contain a variety of information based on deep learning algorithms that extract textual (evaluative) information and metadata from the Web.

Hegelian Conjunction, Hegelian Contradiction - Ficara, Elena; Beall, Jc (History and Philosophy of Logic)

The Formalization of Dialectics - Ficara, Elena; Priest, Graham (History and Philosophy of Logic)

Steady-State Error Compensation for Reinforcement Learning-Based Control of Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Safe Reinforcement Learning-Based Control in Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (2023 International Conference on Future Energy Solutions (FES))

Ernährungsarmut unter Pandemiebedingungen - Birner, Regina; Linseisen, Jakob; Arens-Azevedo, Ulrike; Balmann, Alfons; Biesalski, Hans Konrad; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kay-Uwe; Iweala, Sarah; Martínez, José; et al. (Berichte über Landwirtschaft)
Ernährungsarmut wird als Problem in Deutschland weitgehend vernachlässigt. Von materieller Ernährungsarmut betroffen sind Menschen, denen es aufgrund fehlender finanzieller Mittel nicht möglich ist, sich gesundheitsfördernd zu ernähren. Etwa 3,5 % der Bevölkerung (rund drei Millionen Menschen) sind durch materielle Ernährungsarmut gefährdet. Damit einher geht oft auch soziale Ernährungsarmut, die Menschen von der sozialen Teilhabe ausschließt, die z. B. durch gemeinsames Essen ermöglicht wird. Essen ist nicht nur von Bedeutung für die körperliche Gesundheit, sondern auch zentral für die psychische Gesundheit und das Wohlbefinden sowie für die soziale Zugehörigkeit, was sich wiederum auf die körperliche Gesundheit auswirkt. Die sozialen Funktionen des Essens werden vielfach übersehen – und bei der Berechnung des Regelbedarfs ausgeblendet. Gerade die Corona-Pandemie hat gezeigt, wie fehlende soziale Kontakte und sozialer Ausschluss sich auf die physische, psychische und soziale Gesundheit auswirken können. Aus Sicht des WBAE (Wissenschaftliche Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucherschutz) ist deshalb der integrative Blick auf die materielle und soziale Ernährungsarmut zentral, da sie sich gegenseitig verstärken können. Diese Stellungnahme befasst sich mit der Frage, wie sich die Corona-Pandemie auf von Ernährungsarmut gefährdete Menschen ausgewirkt hat und was daraus gelernt werden kann. Ein wichtiger Aspekt ist der zeitweilige Wegfall von Essensangeboten in Kitas, Schulen, Tafeln und anderen karitativen Essensangeboten, die ein Sicherheitsnetz für Menschen in Ernährungsarmut darstellen. Die Stellungnahme zieht auf dieser Basis auch Schluss-folgerungen zur Ernährungsarmut außerhalb von Pandemiebedingungen. Im Hinblick auf die Notwendigkeit der Vermeidung von Fehlernährung in Haushalten, die von Ernährungsarmut bedroht sind, kommt der WBAE zu dem Schluss, dass diese Risikogruppe während der Pandemie nicht ausreichend im Fokus der Maßnahmen zur Abmilderung der Pandemiefolgen stand. Dies zeigt sich schon daran, dass kaum Daten erhoben wurden. Deutschland verfügt über kein klares Indikatoren- und Zielsystem und kein Monitoring zur Ernährungsarmut. Die wenigen vorhandenen Daten weisen auf problematische Entwicklungen hin. Insgesamt wurden durch den Bund sehr umfangreiche Mittel zur Bewältigung der wirtschaftlichen und sozialen Folgen der Corona-Pandemie und zur Einkommenssicherung während der Pandemie eingesetzt. Dies ist unter dem Blickwinkel „Ernährungsarmut” positiv zu bewerten. Es ist davon auszugehen, dass diese Maßnahmen verhindert haben, dass noch mehr Haushalte von Ernährungsarmut betroffen waren. Insgesamt zeigt die Analyse jedoch, dass es kaum gezielte Maßnahmen gab, um den Ausfall von Kita- und Schulernährung durch alternative Formen der Bereitstellung von Lebensmitteln oder einer warmen Mahlzeit aufzufangen. Maßnahmen auf Bundesebene fehlten, um Länder, Kommunen und nicht-staatliche Organisationen dabei zu unterstützen. Auswertungen der Pandemiemaßnahmen vergleichbarer Länder zeigen, dass dort schnelle und flexible Maßnahmen zur Bereitstellung von Lebensmitteln eine wichtige Rolle gespielt haben, um armutsgefährdete Haushalte zu unterstützen. In Deutschland wurden vorwiegend finanzielle Transfers genutzt, z. T. zeitlich verzögert und wenig zielgruppenspezifisch. Vor diesem Hintergrund hat der WBAE mögliche Maßnahmen gegen Ernährungsarmut – in Krisen, aber auch generell – untersucht: (1) finanzielle Transfers (einmalig oder fortlaufend), (2) Lebensmittelgutscheine („Voucher“), (3) Lebensmittelpakete und (4) warme Mahlzeiten, wobei die letzten beiden Optionen jeweils zur Abholung oder zur Auslieferung angeboten werden können. Die untersuchten internationalen Beispiele zeigen Möglichkeiten, wie z. T. mit schnellen und teilweise innovativen Ansätzen auf Lockdown-Maßnahmen reagiert wurde. Im Grundsatz spricht aus Sicht des WBAE aber vieles für das deutsche System zur Bekämpfung der Ernährungsarmut, das im Kern auf einem Bürgergeld beruht. Ein solches Bürgergeld muss jedoch ausreichend sein, um materielle und soziale Ernährungsarmut zu vermeiden. Die aktuellen, im Bürgergeld für Essen und Getränke zur Verfügung stehenden Beträge entsprechen allerdings nicht diesem Anspruch. Bei der Einführung des Bürgergelds im Jahr 2023 wurde zwar zeitnah auf die hohe Inflation reagiert. Die Berechnungsmethodik für die Bedarfsermittlung wurde aber nicht angepasst, sodass der Regelsatz nach wie vor nicht für eine gesundheitsfördernde Ernährung ausreicht. Die soziale Funktion von Ernährung wird bei der Berechnung des Regelsatzes nicht berücksichtigt. Um bei akutem Handlungsbedarf, wie z. B. auch bei der derzeitigen Inflation, schneller reagieren zu können, sollten außerdem Systeme zur Auszahlung sozial differenzierter „Krisentransfers” an vulnerable Haushalte mit geringem Verwaltungsaufwand ermöglicht werden. Darüber hinaus sollte für den zentralen Bereich der Kinder-ernährung der Schutz einer adäquaten Grundsicherung durch einen Systemwechsel zu einer integrativen, beitragsfreien und somit nicht-diskriminierenden Kita- und Schulverpflegung ergänzt werden, die zudem den DGE-Qualitätsstandards entspricht. Schließlich sollte der Staat privates, ehrenamtliches Engagement ergänzend fördern, z. B. durch Infrastrukturunterstützung bei karitativen Essensangeboten. Eine Herausforderung der Gestaltung von karitativen Lebensmittelangeboten besteht darin, dass sie oft als stigmatisierend und beschämend wahrgenommen werden und der Nachweis eines Anspruches teils schwierig ist. Zudem bestehen oft nur wenige Wahlmöglichkeiten, sodass individuelle Präferenzen oder Unverträglichkeiten nur sehr eingeschränkt berücksichtigt werden können. Im Hinblick auf die soziale Dimension der Ernährung kommt hinzu, dass wichtige soziale Funktionen des Essens, wie das gemeinsame Essen, also Kommensalität, nicht oder nur sehr eingeschränkt ermöglicht wird. Auch bleiben diejenigen, die versorgt werden, dabei meist unter sich. Vor dem Hintergrund dieser Gesamteinschätzung empfiehlt der WBAE die folgenden, in Abbildung Z 1 dargestellten Maßnahmen (siehe Beitrag). Zusammenfassend betont der WBAE die in Deutschland weiterhin unterschätzten Risiken materieller und sozialer Ernährungsarmut. Im Rahmen der geplanten Nationalen Ernährungsstrategie der Bundesregierung sollte dem Thema Ernährungsarmut aus Sicht des WBAE eine herausgehobene Bedeutung zugemessen werden.

Perspective: A Conceptual Framework for Adaptive Personalized Nutrition Advice Systems - Renner, Britta; Buyken, Anette; Gedrich, Kurt; Lorkowski, Stefan; Watzl, Bernhard; Linseisen, Jakob; Daniel, Hannelore; Conrad, Johanna; Ferrario, Paola G.; Holzapfel, Christina; Leitzmann, Michael; Richter, Margrit; et al. (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

CYLENCE: Strategies and Tools for Cross-Media Reporting, Detection, and Treatment of Cyberbullying and Hatespeech in Law Enforcement Agencies - Kaufhold, Marc-André; Bayer, Markus; Bäumler, Julian; Reuter, Christian; Stieglitz, Stefan; Basyurt, Ali Sercan; Mirbabaie, Milad; Fuchß, Christoph; Eyilmez, Kaan (Mensch und Computer)

Improving the End-of-Line Test of Custom-Built Geared Motors using Clustering based on Neural Networks - N., N.